Therapeutic Effect of BDNF-Overexpressing Human Neural Stem Cells (HB1.F3.BDNF) in a Rodent Model of Middle Cerebral Artery Occlusion. Issue 8 (August 2013) - Chang, Da-Jeong; Lee, Nayeon; Choi, Chunggab; Jeon, Iksoo; Oh, Seung-Hun; Shin, Dong Ah; Hwang, Tae-Sun; Lee, Hong J.; Kim, Seung U.; Moon, Hyeyoung; Hong, Kwan Soo; Kang, Kyung-Sun; et al.
Ischemic stroke mainly caused by middle cerebral artery occlusion (MCAo) represents the major type of stroke; however, there are still very limited therapeutic options for the stroke-damaged patients. In this study, we evaluated the neurogenic and therapeutic potentials of human neural stem cells (NSCs) overexpressing brain-derived neurotrophic factor (HB1.F3.BDNF) following transplantation into a rodent model of MCAo. F3.BDNF human NSCs (F3.BDNF) were transplanted into the contralateral side of striatum at 7 days after MCAo, and the transplanted animals were monitored up to 8 weeks using animal MRI and various behavioral tests before they were sacrificed for immunohistochemical analysis. Interestingly, animal MRI results indicate that the majority of contralaterally transplanted neural stem cells were migrated to the peri-infarct area, showing a pathotropism. Transplanted animals exhibited significant behavioral improvements in stepping, rotarod, and modified neurological severity score (mNSS) tests. We also found that the transplanted human cells were colocalized with nestin, DCX, MAP2, DARPP-32, TH, GAD65/67-positive cells, of which results can be correlated with neural regeneration and behavioral recovery in the transplanted animals. More importantly, we were able to detect high levels of human BDNF protein expression, presumably derived from the transplanted F3.BDNF. Taken together, these results provide strong evidence that human neural stem cells (F3.BDNF) are effective in treating stroke animal models.